A survey on skills for cone beam computed tomography interpretation among endodontists for endodontic treatment procedure - Krishnamachari Janani; Raghu Sandhya (Wolters Kluwer Medknow Publications, 2019)
Introduction: Cone beam computed tomography (CBCT) is used as a diagnostic tool, which aids in deciding the treatment plan in various fields of dentistry. In endodontics, CBCT is a useful tool in diagnosing apical periodontitis, resorptions, perforation, root canal morphology, traumatic injuries, and voids. The objective of this study was to evaluate the knowledge attitude and practice in diagnosing and interpreting the endodontic treatment using CBCT among the endodontists. Materials and Methods: A cross-sectional questionnaire survey was conducted among endodontists. Overall, 97 participants were included in the survey and the questionnaire containing 15 closed-ended questions was administered to the participants. Descriptive statistics were used to analyze the data. Results: On analyzing the response to the questionnaire, it was found that out of 97 participants, 24 had professional experience of more than 10 years. About 57% of participants preferred using digital radiographic technique for diagnosis. Majority of them were aware that CBCT is used for identifying location, size, and extent of periapical lesions. About 46% of participants stated that in detecting voids, CBCT was thrice significant compared with periapical radiography. According to 31% of the endodontists, CBCT was not reliable to detect vertical root fracture. It was found that 63% of the endodontists said they have not undergone any training or workshop in CBCT. Conclusion: This research study revealed that adequate training and skills are required in interpreting CBCT in endodontic treatment procedure among endodontists.